2016
DOI: 10.1123/ijspp.2015-0238
|View full text |Cite
|
Sign up to set email alerts
|

Running Mechanics During the World’s Most Challenging Mountain Ultramarathon

Abstract: The aim of study was to examine the effects of the world's most challenging mountain ultramarathon (Tor des Géants [TdG]) on running mechanics. Mechanical measurements were undertaken in male runners (n = 16) and a control group (n = 8) before (PRE), during (MID), and after (POST) the TdG. Contact (tc) and aerial (ta) times, step frequency (f), and running velocity (v) were sampled. Spring-mass parameters of peak vertical ground-reaction force (Fmax), vertical downward displacement of the center of mass (Δz), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
46
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 28 publications
7
46
0
2
Order By: Relevance
“…However, we tried to control that effect recording the kinematics data from 3 min into each condition, to give subjects time to be as comfortable as possible during the locomotion. Finally, even though an extreme MUM as the one from the present study leads to physiological, neuromuscular and mechanics alterations due to fatigue (e.g., Saugy et al, 2013; Vernillo et al, 2014b, 2015a; Degache et al, 2016), the non-inclusion of a control group may leave the present results susceptible to time or order effects. However, we believe that this study provides the opportunity to explore the adaptive responses of humans submitted to the extreme load and stress induced by a 330-km race with a cumulative elevation gain of +24,000 m but it must be seen as a first step toward comprehension of the physiological and biomechanics consequences of exercise as extreme as mountain ultra-marathons.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…However, we tried to control that effect recording the kinematics data from 3 min into each condition, to give subjects time to be as comfortable as possible during the locomotion. Finally, even though an extreme MUM as the one from the present study leads to physiological, neuromuscular and mechanics alterations due to fatigue (e.g., Saugy et al, 2013; Vernillo et al, 2014b, 2015a; Degache et al, 2016), the non-inclusion of a control group may leave the present results susceptible to time or order effects. However, we believe that this study provides the opportunity to explore the adaptive responses of humans submitted to the extreme load and stress induced by a 330-km race with a cumulative elevation gain of +24,000 m but it must be seen as a first step toward comprehension of the physiological and biomechanics consequences of exercise as extreme as mountain ultra-marathons.…”
Section: Discussionmentioning
confidence: 63%
“…It has been previously shown that after completing a 166-km (Morin et al, 2011) and a 330-km (Degache et al, 2016) MUM the subjects modified their running step mechanics and spring-mass behavior, leading to a “smoother” and “safer” running style associated with an overall lower impact. These observations have also been reported after 5 h of hilly running (Degache et al, 2013) and an uphill marathon (Lazzer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the reverse may be true in response to slower velocity, longer duration running. Several studies have reported reductions in leg stiffness and minimal change in vertical stiffness following fatiguing protocols (Degache et al, 2016;Hayes and Caplan, 2014;Rabita, Couturier, Dorel, Hausswirth, & Le Meur, 2013;Rabita, Slawinski, Girard, Bignet, & Hausswirth, 2011).…”
Section: Running Gaitmentioning
confidence: 99%
“…Fatigue-induced changes in running technique were previously observed after this eUT. 3,20 To avoid mechanical changes potentially biasing interpretation of the results, cycling was used to focus only on metabolic adaptations.…”
mentioning
confidence: 99%